Mathematics in the Spanish press: a case study of the 18th century journal Semanario de Salamanca - María José Madrid; Carmen León-Mantero; Jose Carlos Casas-Rosal; Alexander Maz-Machado (Humanities & Social Sciences Communications, 2023)
Abstract Old mathematics books and textbooks have always been sources of relevant information for researchers working on the history of mathematics and mathematics education. However, helpful information about this field can also be found in journals, ministerial decrees, or notes. Consequently, this article analyzes the contents related to mathematics or mathematics education in an 18th-century weekly journal published in the Spanish city of Salamanca, Semanario de Salamanca. To this end, we conducted a qualitative and descriptive investigation using a content analysis technique, which is widely used in research in this related area. Our results show that despite the fact that the weekly publication under investigation was specialized neither in mathematics nor in science, it included mathematical problems and solutions, mathematical texts, job advertisements for mathematics teachers, mathematics book reviews, and opinions about mathematics. Therefore, the present work expands knowledge of the presence and dissemination of mathematics and mathematics education in 18th-century Spanish society.